G198(P) Neonatal haemochromatosis – clinical case presentation, diagnosis and response to treatment. (24th May 2017) - Basu, A; Nedungadi, S; Dady, I; Mahaveer, A
Abstract : Aim: Neonatal haemochromatosis is a rare clinical condition to present with acute liver failure in newborn period. This causes congenital cirrhosis or acute liver failure with and without iron overload and siderosis. Aim is to discuss their clinical presentations, diagnosis, response to treatment and outcome of infants with neonatal Haemochromatosis (NH) from a tertiary neonatal unit. Methods: Review of local database registry and notes of babies who are diagnosed with NH in our neonatal unit. Results: Three babies have been diagnosed with NH. Two babies are from same family and are siblings. All babies were born preterm around 33 weeks. Two babies had IUGR at birth. The median birth weight is 1700 grams. Two babies presented with acute liver failure and coagulopathy from birth and one baby presented with sepsis and liver failure in second week of life. They all had deranged liver function tests, coagulopathy with increased PT/APTT. All had elevated ferritin and alpha feto protein. Ultrasound of the abdomen showed irregular nodules and a heterogeneous echo texture of the liver. All three babies had abnormal head scans with bilateral intraventricular haemorrhages and increased white matter echogenicities. Salivary gland biopsy on one of the siblings showed iron deposition which confirmed NH. This infant had double volume exchange therapy and immunoglobulin and the liver functions are returning to normal. Two babies passed away with multi organ failure Post-mortem examination showed extrahepatic siderosis. Conclusion: Neonatal haemochromatosis is a rare condition due to maternal alloimmunity resulting in fetal liver injury. Early diagnosis and early treatment is crucial for survival. Identification of infants with NH is important as treatment is available and effective for subsequent pregnancies.Pre-natal diagnosis can be made by recognising the nodular liver and hydrops on fetal US and MR. IVIG therapy during pregnancy (18 weeks GA onwards) and after birth is shown to be effective in preventing the need of liver transplant, reduces mortality and even full recovery in some cases.